O lazer de atletas com deficiência física: “da casa para a rua” - Renan Jorge Ramos Martins (2022)
Thinking about the leisure of people with physical disabilities who carry in their bodies their singularities, several possibilities of being human, and associated to the practice of paralympic sports activities is a complex work. The bodies of people with disabilities have been marked, throughout time, by exclusion, segregation, integration, and continue being marked by the struggle for inclusion. Inclusion to participate in social spaces, be they leisure, sports, education, work, and health, which still do not promote accessibility, in its broadest sense, which goes beyond physical structures, as well as conditions that allow a diverse social participation. "How do people with physical disabilities practicing paralympic sport experience leisure?" was the question that problematized the research, so as to achieve the main objective of "verifying the perception of paratheletes about how the experience with paralympic sport influenced their leisure experiences". Through the narrative interview instrument proposed by the (auto)biographical research method. Having as a motto "Nothing about us, without us", the established method was an attempt to carry out an emancipatory research, which has one of its characteristics research methods that encompass the experience of disability. To this end, the people with physical disabilities, athletes in paralympic sports, by sharing their stories or part of them, took on the main role in the research, with stories told and lived by them with the practice of paralympic sports made possible by an Association for people with physical disabilities. Stories of achievements, difficulties, and dreams, in a reflection process of what it is to be and to become an athlete. The narratives bring up the most varied possibilities of experiencing leisure, such as contemplating nature; being entertained; going out and drinking with friends; watching movies; cooking; barbecuing with the family; listening to music; traveling; dating; resting and doing nothing, besides training for the sport, doing physical therapy, and studying. It was observed that leisure possibilities outside the home are expanded and mediated by the Association for people with physical disabilities. The activities and social relationships promoted by the Association encouraged people with physical disabilities to go out more. The practice of sports means life for the athletes, they have the opportunity to (re)build their lives, they have the chance to be motivation for someone who still thinks they can't do anything, due to the prejudice that is the result of the disability rooted in society. Together with the NGO, families, especially mothers, form a stronger support and care network for people with disabilities. And the engagement to practice sports is the achievement of confidence to perform daily life activities in a more autonomous way, as well as the acquisition of physical strength and material goods, made possible the maintenance of physical and mental health balance, and the achievement of a profession, that of an athlete. The lack of accessibility was a unanimous finding during trips to competitions and to perform activities of daily living. The discourse of normality that treats a different body with inferiority, a capacitating discourse that limits the existence of people with disabilities, was also present in the narratives. We conclude that paralympic sports, promoted by an Association for people with disabilities, may be an entrance door to the leisure experiences of these people, it is a stimulus for them to leave home, get to know and experience the most diverse leisure possibilities. In addition to enabling people with disabilities to occupy spaces which, even today, are still designated to only one way of being, the one based on the biological "normality" standard, which segregates and rejects diversity.